Reframing Visa on Arrival Policy within Non-Military Defense Management: Security Governance in DKI Jakarta - Miyaki Natanael; Priyanto Priyanto; Editha Praditya (Digital Innovation : International Journal of Management, 2026)
This study examines the implementation of Indonesia’s Visa on Arrival (VoA) policy in DKI Jakarta as both an instrument of tourism-driven economic recovery and a component of non-military national defense management under Law No. 23 of 2019 on the Management of National Resources for National Defense. While VoA has significantly contributed to the rebound of international tourist arrivals—surpassing 11 million visits nationally in 2023—it simultaneously generates governance challenges at strategic entry points such as Soekarno–Hatta International Airport, where facilitation of mobility intersects with risks including overstaying, transnational crime, human trafficking, and potential infiltration by non-state actors. Existing scholarship largely emphasizes economic impacts and regulatory frameworks, leaving limited analysis of VoA as part of an integrated civil defense infrastructure. Addressing this gap, the study aims to analyze how VoA implementation in DKI Jakarta is managed within a non-military defense perspective, particularly regarding institutional coordination, immigration intelligence, and risk mitigation mechanisms. Employing a qualitative case study approach, data were collected through in-depth interviews with immigration officials and security stakeholders, document analysis of relevant laws and ministerial regulations, and review of official immigration statistics, followed by thematic analysis. The findings indicate that although VoA effectively supports economic and diplomatic objectives, its function as a non-military defense instrument remains constrained by fragmented inter-agency coordination, uneven intelligence integration, and limited adaptive governance capacity at the local level. Strengthening collaborative surveillance systems, data-sharing mechanisms, and strategic policy alignment between immigration authorities and national defense institutions is therefore essential. The study concludes that reframing immigration governance as part of Indonesia’s broader non-military defense strategy is crucial to balancing openness with security in high-density international gateways.